'It is important at this point to make clear that this study is not "anti-iPad"': Ed-Tech speak around iPads in educational technology research. Issue 2 (3rd April 2021) - Mertala, Pekka
ABSTRACT: This position paper contributes to the field of critical educational technology (Ed-Tech) research by providing empirical evidence for the qualities of the phenomenon known as Ed-Tech speak. The research question, how does Ed-Tech speak in research articles about Apple's iPad contribute to promoting and validating the importance and utility of the iPad for teaching and learning, is addressed by applying critical genre analysis to investigate empirical research articles discussing the use of iPads in institutional education. As a result, four categories were formed: the self-evident importance of iPads, overgeneralization of references, the use of strong reporting verbs (to boost weak references), and the use of boosting devices when discussing the findings. Possible explanations for the existence of Ed-Tech speak in research articles are offered.